Nitrogen reduction combined with ETc irrigation maintained summer maize yield and increased water and nitrogen use efficiency - Gu, Limin; Mu, Xinyuan; Qi, Jianshuang; Tang, Baojun; Zhen, Wenchao; Xia, Laikun (Frontiers in Plant Science, 2023)
High rainfall and excessive urea application are counterproductive to summer maize growth requirements and lower grain yield and water/nitrogen (N) use efficiency. The objective of this study was to determine whether ETc-irrigation based on maize demand and reducednitrogenrate in the Huang Huai Hai Plain increased water and nitrogen use efficiency without sacrificing summer maize yield. To achieve this, we conducted an experiment with four irrigation levels [ambient rainfall (I0) and 50% (I1), 75% (I2) and 100% (I3) of actual crop evapotranspiration (ETc)] and four nitrogen rates [no nitrogen fertilizer (N0), recommended nitrogen rate of urea (NU), recommended nitrogen rate of blending controlled-release urea with conventional urea fertilizer (BCRF) (NC), and reduced nitrogen rate of BCRF (NR)] in 2016-–2018. The result show that reduced irrigation and nitrogen rate reduced Fv/Fm, 13C-photosynthate, and nitrogen accumulation both in the kernel and plant. I3NC and I3NU accumulated higher 13C-photosynthate, nitrogen, and dry matter. However, 13C-photosynthate and nitrogen distribution to the kernel were decreased from I2 to I3 and were higher in BCRF than in urea. I2NC and I2NR promoted their distribution to the kernel, resulting in a higher harvest index. Compared with I3NU, I2NR increased root length density by 32.8% on average, maintaining considerable leaf Fv/Fm and obtaining similar kernel number and kernel weight. The higher root length density of I2NR of 40–60 cm promoted 13C-photosynthate and nitrogen distribution to the kernel, as well as increased the harvest index. As a result, the water use efficiency (WUE) and nitrogen agronomic use efficiency (NAUE) in I2NR increased by 20.5–31.9% and 11.0–38.0% than I3NU, respectively. Therefore, 75%ETc deficit irrigation and BCRF fertilizer with 80% nitrogen rate improved root length density, maintained leaf Fv/Fm in the milking stage, promoted 13C-photosynthate, and nitrogen distributed to the kernel, ultimately providing a higher WUE and NAUE without significantly reducing grain yield.